Enhanced response to dabrafenib plus trametinib in a patient with BRAFV600E lung cancer harboring an RNF43 variant of unknown significance: a case report - D’Argento, Ettore; Vitale, Antonio; Russo, Jacopo; Minucci, Angelo; Cancellieri, Alessandra; Stefani, Alessio; Monaca, Federico; Horn, Guido; Occhipinti, Denis; Troisi, Paola; Scala, Alessandro; Polidori, Sara; et al. (Frontiers in Oncology, 2025)
BackgroundLiterature evidence reports that RNF43 (ring finger protein 43) gene mutations could serve as predictive biomarkers of response to certain anti-cancer therapies. To delve deeper into the specific role of RNF43 mutations in lung cancer and their relevance to therapy response, we provide the first report of marked efficacy of the dabrafenib and trametinib therapeutic combination in a patient with microsatellite-stable (MSS) non-small-cell lung cancer (NSCLC) with BRAFV600 and RNF43 mutations.Case descriptionAn 85-year-old patient was diagnosed with NSCLC with the presence of MSS, BRAFV600E and RNF43 mutations. The patient started the combination treatment with dabrafenib and trametinib, soon reporting an overall clinical benefit. A contrast-enhanced cranio–thorax–abdomen CT scan performed after 1 month of therapy reported a sharp reduction in lung cancer and hilo-mediastinal lymphadenomegaly; the central colliquation of the left adrenal metastasis was also reported. After 9 months of therapy, the cranio-thorax-abdomen CT scan with contrast medium confirmed the reduction of the adenocarcinoma, with residual scarring component; the right adrenal lesion was not visible, and the contralateral lesion was stable. At the last follow-up (February 2024), the global clinical condition of the patient was good; she was autonomous, and oxygen therapy was not necessary.ConclusionsOur clinical case represents the first report of marked efficacy of the dabrafenib–trametinib combination reported in an 85-year-old patient diagnosed with NSCLC with the presence of MSS, BRAFV600E and RNF43 mutations. This supports the hypothesis on the relevance of RNF43 mutations in predicting the clinical benefit of targeted therapies and in modulating the anti-tumor activity of anti-BRAF therapies, suggesting that RNF43 mutations represent a promising biomarker that warrants further validation for its potential to help prioritize therapy combinations in selected lung cancer patients.